ETIKA KOMUNIKASI BIDAN DALAM PERSPEKTIF RUANG PUBLIK - Wiriya Tantra, Manggala; Wanti, Dida (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
Communication is a very important indicator in facilitating health services by midwives, so ethics in communication really need to be considered. The purpose of this study is to describe the communication ethics of midwives in the perspective of public space which is expected to provide benefits and knowledge to the community, especially various parties with an interest in midwives. Literature study is the method used in this research. In the perspective of public space, midwife communication ethics can be understood as a way of communicating midwives as health workers with clients to convey the purpose of health services through dialogue in order to obtain mutual agreements that do not harm clients and do not violate the midwife code of ethics. In this case, the public space is seen as a place where clients and midwives can discuss any concerns. In public space, birth attendants and clients can communicate opinions or conclusions openly and transparently. Moral correspondence in the public sphere can talk about whatever is desired and when all feelings have been expressed, then at that time it will lead to a certain choice, which is the best health service.